Spatial-Statistical Analysis of the Relationship Between Population Density and the Distribution of Active Cooperatives in Jember Regency, Indonesia - Muhammad Nurul Huda; Azril Chairil; Rafi Sulthan Rizqullah; Solihan; Shalsabilla Aulia Putri; Denisa Aulia Pratiwi; I Putu Indra Pramana Putra (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2026)
This study examines the spatial and statistical relationship between population density and the distribution of active cooperatives across 31 sub-districts in Jember Regency, Indonesia. Using secondary data from 2024, the research applies a quantitative approach that integrates spatial mapping with statistical analysis. The Shapiro–Wilk normality test indicates that both population density and the number of active cooperatives are not normally distributed (p < 0.05). Therefore, Spearman Rank correlation analysis is employed, revealing a statistically significant but weak positive relationship (r = 0.391, p = 0.030). Spatial patterns show that urban sub-districts such as Kaliwates and Sumbersari exhibit high concentrations of both population density and cooperative activity. However, several agrarian districts with relatively low population density, including Ambulu and Puger, also demonstrate a high number of active cooperatives. These findings indicate that while population density provides an important market base, the spatial distribution of cooperatives in Jember Regency is also strongly shaped by local economic structures and agrarian production systems rather than demographic factors alone.